Development of a Russian version of the Minnesota low vision reading chart - I.R. Stepanets; A.N. Kulikov; S.A. Koskin; D.I. Zhilchuk (РМЖ "Клиническая офтальмология")
I.R. Stepanets1, A.N. Kulikov2, S.A. Koskin2, D.I. Zhilchuk2 1ZRENIE Ophthalmological Clinical Center, St. Petersburg, Russian Federation 2S.M. Kirov Military Medical Academy, St. Petersburg, Russian Federation Background: to evaluate reading performance and to obtain comparable results in multi-center studies carried out in several countries, it is necessary to use rigorously developed standardized tests in different languages. Aim: to develop a Russian version of the Minnesota low vision reading chart (MNREAD) and to test it for measuring the near vision reading performance in normally sighted young adults. Patients and Methods: sixty sentences were composed using the most common words selected from the frequency dictionary and the school curriculum of 1st — 4th grades. The number of characters per sentence and the sentence length were adapted to match the MNREAD design principles. 38 sentences were selected. Then, two versions of the test in Russian language (MNREAD-R) with different series of sentences were printed out and tested randomly in 30 subjects aged 18–22 years during one session. The reading parameters were assessed at a 40-cm distance; subjects were asked to read the charts for testing their monocular (right and left eyes) and binocular reading. The measured reading acuity (RA), maximum reading speed (MRS), critical print size (CPS) and reading accessibility index (ACC) were evaluated using statistical analysis. Results: the time taken to read a standardized short test sentence was approx. 3 s. Binocular MRS for test chart 1 was 198±4.51 words/min, for test chart 2 — 200±4.76 words/min; CPS in binocular conditions was the same for both charts and equaled to 0.08±0.02 logMAR; binocular RA for test chart 1 was (-)0.04±0.01 logMAR and test chart 2 — (-)0,06±0,01 logMAR; binocular ACC was 1.00±0.02 and 1.03±0.02, respectively. No statistically significant differences were found between all parameters measured with the use of test charts 1 and 2 (р>0.05). Conclusion: the developed MNREAD-R test charts can be used for Russian speaking population to measure RA, MRS, ACC and RT. Keywords: MNREAD, reading speed, tests to assess reading performance, visual acuity, low vision. For citation: Stepanets I.R., Kulikov A.N., Koskin S.A., Zhilchuk D.I. Development of a Russian version of the Minnesota low vision reading chart. Russian Journal of Clinical Ophthalmology. 2022;22(3):150–155 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-150-155.